Medieval Britain Conquest, Power and People - McAleavy, Tony; Europe; Great Britain (Cambridge University Press, 1991)
The major transition in British society that occurred during the Middle Ages is analyzed from four different perspectives that explore the period's power struggles, economic aspects, ideas & beliefs & medieval culture.
Keywords: Arts & Humanities; Education; History; Teaching Methods & Materials